Condensation heat transfer of a hybrid hydrophilic–hydrophobic surface with different arrangements. Issue 4 (3rd April 2023) - Foshat, Saeed; Jafarpur, Khosrow; Yaghoubi, Mahmood
Abstract: Condensation, a process in which the phase changes from vapor to liquid, plays a crucial role in various industrial systems. So far, several techniques have been proposed to improve the characteristics of condensation. The manipulation of the wettability of a surface is a novel scheme which reduces the heat resistance of the droplets on the surface. The present study experimentally explored the effect of hybrid hydrophilic–hydrophobic surfaces on the formation of primary nucleation, the movement of droplets, and heat transfer. The hydrophobic and hybrid surfaces fabricated by sol-gel and deep coating method. Three distinct surfaces were considered including (i) a hydrophobic surface, (ii) a hybrid hydrophilic–hydrophobic surface with a vertical arrangement (HHSVA), and (iii) a hybrid hydrophilic–hydrophobic surface with a horizontal arrangement (HHSHA). It was found that the HHSVA markedly enhanced the heat and mass transfer compared with the hydrophobic and the HHSHA configurations. Compared with that of the hydrophobic surface, the heat transfer of the HHSVA and the HHSHA increased by 31.9% and decreased by 25.9%, respectively. Then, the heat transfer on these hybrid surfaces depends on the orientation of surfaces. The optimized orientation can increase the heat transfer and improve the droplet's dynamic parameter on hybrid surfaces.